Evaluation of Hematological and Biochemical Parameter Changes in MDR-TB Patients Undergoing OAT Treatment at RSUD Anutapura Palu in 2022-2025 - indriani; Andi Meutia Ilhamjaya; Andrini Suryana Mangopa; Tri Fadila Maharani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Multidrug-resistant tuberculosis (MDR-TB) is a major challenge in the control of tuberculosis in Indonesia. Long-term treatment with anti-tuberculosis drugs (OAT) is known to cause significant side effects on hematological and biochemical functions. This study aims to evaluate changes in leukocyte count, neutrophil-lymphocyte ratio (NLR), hematocrit, platelet count, hemoglobin, SGOT, SGPT, urea, and creatinine levels in MDR-TB patients undergoing OAT treatment at RSUD Anutapura Palu during the period of 2022-2024. The research employed a retrospective cohort design using secondary data from patient medical records. The results showed a decrease in leukocytes, NLR, platelets, and hemoglobin, as well as an increase in SGOT, SGPT, urea, creatinine and hematocrit after treatment. This study emphasizes the importance of regular monitoring for OAT side effects to improve treatment effectiveness and patient safety.